Treatment method for optimizing nickel-based high-temperature alloy grain boundary and nickel-based high-temperature alloy
The high proportion of Σ3 grain boundaries are formed through pulse current processing, and the microstructure of nickel-based high-temperature alloys is optimized, which solves the problem of poor plasticity in laser additive manufacturing, and significantly improves the plasticity and service life of the alloy.
Patent Information
- Application Number
- CN202510321113.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-07-04
AI Technical Summary
In the prior art, laser additive manufacturing nickel-based high-temperature alloys have poor plasticity, and traditional heat treatment methods are difficult to improve their microstructure, resulting in poor plasticity in medium and low-temperature service environments, limiting their service life.
The pulse current treatment method is adopted to promote the generation of annealing twins by forming a high proportion of Σ3 grain boundaries, and optimize the microstructure of nickel-based high-temperature alloys, including adjusting the alloy composition and controlling pulse current parameters, such as current density, frequency, duty cycle and processing temperature, to eliminate the Laves phase, reduce stacking fault energy, and improve grain boundary mobility.
Significantly improve the plasticity and service life of nickel-based high-temperature alloys, improve the strength and toughness of the alloys by increasing the Σ3 grain boundary ratio and optimizing the microstructure, reduce the risk of grain coarseness, and extend the service life.
Smart Images

Figure CN120243966A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nickel-based superalloys, and particularly relates to a method for optimizing grain boundaries of nickel-based superalloys and nickel-based superalloys. Background Art
[0002] The 718Plus superalloy is a precipitation-strengthened nickel-based superalloy with excellent comprehensive mechanical properties and good processing performance, and is mainly applied to hot-end components such as aeroengine casings, compressor blades, fasteners, and turbine disks.
[0003] With the development of aeroengines, traditional processing techniques are difficult to meet the increasing requirements for high dimensional accuracy and complex-structured components. Therefore, laser melting deposition (LMD) is usually used to manufacture 718Plus superalloy components. There are significant textures and relatively large columnar crystal structures in the 718Plus superalloy manufactured by LMD. Among them, the significant textures lead to differences in the properties of the material in different directions, that is, anisotropy, which is extremely disadvantageous in application scenarios with high requirements for performance consistency. In addition, in medium and low temperature service environments, grain boundary strengthening is usually used to improve the strength and plasticity of the alloy. However, coarse grains (relatively large columnar crystal structures) are likely to cause cracks in the alloy, greatly reducing the grain boundary strengthening effect, resulting in poor plasticity of the alloy, thus limiting the long-term use of this alloy.
[0004] In order to extend the service life of nickel-based superalloys, existing techniques have improved the microstructure and properties of nickel-based superalloys through appropriate deformation and heat treatment. However, due to the low dislocation density in additively manufactured superalloys, it is difficult to improve their microstructure using existing heat treatment methods, and thus it is difficult to extend the service life of nickel-based superalloys. Summary of the Invention
[0005] Therefore, the present invention provides a method for optimizing grain boundaries of nickel-based superalloys and nickel-based superalloys, which can solve the problem of poor plasticity of nickel-based superalloys manufactured by laser additive manufacturing in the prior art.
[0006] In order to solve the above problems, the present invention provides a method for optimizing grain boundaries of nickel-based superalloys, including the following steps:
[0007] Performing pulsed current treatment on the superalloy to make the proportion of Σ3 grain boundaries in the treated nickel-based superalloy > 50%.
[0008] Furthermore, the nickel-based superalloy is an additively manufactured nickel-based superalloy;
[0009] Preferably, the additively manufactured nickel-based superalloy is prepared by a laser melting deposition process;
[0010] Further preferably, the parameters of the laser melting deposition process are as follows: the laser power is 900 - 1000 W; the laser scanning speed is 8 - 10 mm / s; the powder feeding rate is 6 - 7 g / min; the Z-axis lifting height is 0.7 - 0.9 mm.
[0011] Further, by weight percentage, the chemical composition of the nickel-based superalloy is: Al 1.5 wt% - 3.6 wt%, Ti 0.5 wt% - 1.5 wt%, Nb 5 wt% - 6 wt%, W 0.5 wt% - 1.5 wt%, Mo 2.5 wt% - 3.5 wt%, Co 9 wt% - 10 wt%, Cr 17 wt% - 19 wt%, Fe 9 wt% - 11 wt%, C 0.02 wt% - 0.03 wt%, and the balance is Ni.
[0012] Further, the parameters of the pulsed current treatment are as follows:
[0013] The current density is 500 - 600 A / mm 2 ; the current frequency is 50 - 5000 Hz; the duty cycle is 10 - 50%; the treatment temperature is 1080 - 1120 °C; the treatment time is 10 - 20 min.
[0014] Further, before the step of performing pulsed current treatment on the superalloy, it further includes:
[0015] Processing the superalloy into a sample with a set size;
[0016] Preferably, a wire electrical discharge machine is used to process the superalloy into a sample with a set size;
[0017] Preferably, the set size is (1.2 - 1.5) mm × (15 - 20) mm × (50 - 55) mm.
[0018] Further, after the step of processing the superalloy into a sample with a set size, it further includes:
[0019] Performing grinding treatment and cleaning treatment on the sample in sequence;
[0020] Preferably, 400 - 800# SiC sandpaper is used to perform grinding treatment on the sample;
[0021] Preferably, acetone is used to perform cleaning treatment on the sample.
[0022] Further, after the step of performing pulsed current treatment on the superalloy, it further includes: cooling treatment on the treated superalloy;
[0023] Preferably, the cooling treatment adopts the method of air cooling of the workpiece.
[0024] On the other hand, the present invention provides a nickel-based superalloy, wherein the proportion of Σ3 grain boundaries in the nickel-based superalloy > 50%; the elongation after fracture of the nickel-based superalloy > 50%.
[0025] Furthermore, the nickel-based superalloy is a processed nickel-based superalloy obtained by using the processing method described in any one of the above.
[0026] Compared with the prior art, the present invention has at least the following beneficial effects:
[0027] 1. On the one hand, the present invention provides a processing method for optimizing the grain boundaries of a nickel-based superalloy, comprising the following steps: performing pulsed current treatment on the superalloy to eliminate the Laves phase in the nickel-based superalloy and making the proportion of Σ3 grain boundaries in the processed nickel-based superalloy > 50%. It should be noted that the present invention promotes the formation of annealing twins through pulsed current treatment, and then forms more Σ3 grain boundaries (the grain boundaries between annealing twins and the matrix grains). Σ3 grain boundaries have lower interfacial energy and higher crack initiation and propagation resistance, so the plasticity of the nickel-based superalloy can be improved, thereby significantly enhancing the service life of the alloy; among them, the pulsed current can, on the one hand, quickly eliminate the Laves phase in the alloy, reduce element segregation, and lower the stacking fault energy (SFE) of the alloy matrix. The lower the stacking fault energy, the lower the energy required to form a stacking fault, so it is easier to form a stacking fault in the material, and the existence of the stacking fault provides a basis for the formation of twins; on the other hand, the Joule heat effect of the pulsed current can increase the temperature of the alloy, reduce the atomic diffusion barrier at the grain boundaries, increase the grain boundary mobility under the non-thermal effect, effectively promote recrystallization nucleation, and is conducive to the formation of high-density annealing twins. At the same time, the Joule heat generated by the pulsed current is released in a short time, and this short-time thermal effect reduces the tendency of interface migration, thereby delaying twin growth and grain coarsening.
[0028] 2. Furthermore, by weight percentage, the chemical composition of the nickel-based superalloy is: Al 1.5 wt% - 3.6 wt%, Ti 0.5 wt% - 1.5 wt%, Nb 5 wt% - 6 wt%, W 0.5 wt% - 1.5 wt%, Mo 2.5 wt% - 3.5 wt%, Co 9 wt% - 10 wt%, Cr 17 wt% - 19 wt%, Fe 9 wt% - 11 wt%, C 0.02 wt% - 0.03 wt%, and the balance is Ni; it should be noted that by adjusting the contents of Al and Ti in the Inconel 718 alloy, reducing the Fe content, and increasing the Co content, the stacking fault energy (SFE) of the alloy is effectively reduced, creating favorable conditions for the formation of annealing twins.
[0029] 3. On the other hand, the present invention provides a nickel-based superalloy obtained by treating with the above method. The proportion of Σ3 grain boundaries in the nickel-based superalloy is > 50%; the elongation after fracture of the nickel-based superalloy is > 50%; among them, the coherent Σ3 grain boundary has a lower interface energy and a higher crack initiation and propagation resistance. Therefore, it is generally considered that introducing more coherent Σ3 grain boundaries in engineering alloys can significantly improve the service life of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. The drawings in the following description are only exemplary. For those of ordinary skill in the art, without creative efforts, other implementation drawings can be obtained according to the provided drawings.
[0031] Figure 1 is the grain boundary distribution diagram of the as-deposited laser additive manufacturing nickel-based superalloy;
[0032] Figure 2 is the comparison diagram of the Σ3 grain boundary proportion of the laser additive manufacturing nickel-based superalloy under different treatment conditions;
[0033] Figure 3 is the comparison diagram of the elongation after fracture of the laser additive manufacturing nickel-based superalloy under different treatment conditions;
[0034] Figure 4 is the grain boundary distribution diagram of the laser additive manufacturing nickel-based superalloy in Example 1 of the present invention;
[0035] Figure 5 is the grain boundary distribution diagram of the laser additive manufacturing nickel-based superalloy in Example 2 of the present invention;
[0036] Figure 6 is the grain boundary distribution diagram of the laser additive manufacturing nickel-based superalloy in Comparative Example 1 of the present invention;
[0037] Figure 7 is the grain boundary distribution diagram of the laser additive manufacturing nickel-based superalloy in Comparative Example 2 of the present invention;
[0038] Figure 8 is the grain boundary distribution diagram of the laser additive manufacturing nickel-based superalloy in Comparative Example 3 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0039] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following will briefly introduce the accompanying drawings required for the description of the embodiments or the prior art. The accompanying drawings in the following description are merely exemplary. For those of ordinary skill in the art, without creative efforts, other implementation drawings can also be obtained based on the provided drawings.
[0040] The present invention provides a method for treating the grain boundaries of a nickel-based superalloy, comprising the following steps:
[0041] The nickel-based superalloy is subjected to pulsed current treatment so that the proportion of Σ3 grain boundaries in the treated nickel-based superalloy is > 50%. Among them, the nickel-based superalloy is an additive manufacturing nickel-based superalloy; the additive manufacturing nickel-based superalloy is prepared by a laser melting deposition process; among them, the laser power is 900 - 1000 w; the laser scanning speed is 8 - 10 mm / s; the powder feeding rate is 6 - 7 g / min; the Z-axis lifting height is 0.7 - 0.9 mm. By weight percentage, the chemical composition of the nickel-based superalloy is: Al 1.5 wt% - 3.6 wt%, Ti 0.5 wt% - 1.5 wt%, Nb 5 wt% - 6 wt%, W 0.5 wt% - 1.5 wt%, Mo 2.5 wt% - 3.5 wt%, Co 9 wt% - 10 wt%, Cr 17 wt% - 19 wt%, Fe 9 wt% - 11 wt%, C 0.02 wt% - 0.03 wt%, and the balance is Ni;
[0042] Among them, the parameters of the pulsed current treatment are: the current density is 500 - 600 A / mm 2 ; the current frequency is 50 - 5000 Hz; the duty cycle is 10 - 50%; the treatment temperature is 1080 - 1120 °C; the treatment time is 10 - 20 min.
[0043] Based on the above method, the present invention promotes the formation of annealing twins through pulse current treatment, thereby forming more Σ3 grain boundaries (grain boundaries between annealing twins and parent grains). The Σ3 grain boundaries have lower interface energy and higher crack initiation and extension resistance, so they can improve the plasticity of nickel-based high-temperature alloys, thereby significantly improving the service life of the alloy; specifically, when the material is subjected to stress, dislocations accumulate at the grain boundaries, increasing the deformation resistance of the material, thereby improving the strength of the alloy. At the same time, the Σ3 grain boundaries can also coordinate the deformation between adjacent grains, promote the initiation of multiple slip systems, make the strain distribution of the material more uniform during the deformation process, avoid local stress concentration, and significantly improve the plasticity and toughness of the alloy. During pulse current treatment, the Joule heating effect causes the local thermal expansion of the alloy to produce stress in the opposite direction of the residual stress, thereby partially offsetting the residual stress. The electron wind force in the non-thermal effect promotes the movement of dislocations, causing dislocations to rearrange, slip and annihilate, effectively relaxing and releasing residual stress. The reduction of residual stress can significantly improve the fatigue performance of the alloy, reduce the initiation and extension of fatigue cracks under alternating loads, and extend the service life of the alloy.
[0044] Among them, on the one hand, the pulse current can quickly eliminate the Laves phase in the alloy, reduce element segregation, and reduce the stacking fault energy (SFE) of the alloy matrix, creating favorable conditions for the formation of annealing twins; on the other hand, the Joule heating effect of the pulse current can increase the temperature of the alloy, reduce the atomic diffusion barrier at the grain boundary, increase the grain boundary mobility, promote the growth of recrystallized grains, and is conducive to the formation of annealing twins.
[0045] It should be noted that by adjusting the Al and Ti contents in the alloy, reducing the Fe content, and increasing the Co content, the stacking fault energy (SFE) of the alloy can be effectively reduced. The lower the stacking fault energy, the lower the energy required to form a stacking fault, so it is easier to form a stacking fault in the alloy. The existence of stacking faults creates favorable conditions for the formation of annealing twins. At the same time, Nb and Mo can also reduce the stacking fault energy of the alloy, but it is easy to form a large number of blocky Laves phases in the alloy. The presence of a large number of blocky Laves phases will cause the continuity of the matrix to be destroyed and become a source of stress concentration. When the alloy is subjected to stress, the stress is concentrated around the Laves phase, which is easy to cause the initiation of cracks, and the Laves phase itself The brittleness of the alloy makes it difficult for the alloy to undergo plastic deformation when subjected to load, limiting the overall plasticity of the alloy. Therefore, pulse current treatment is used to provide energy for the dissolution and re-precipitation of the precipitated phase, and the non-thermal effect promotes atomic diffusion, so that the size, shape and distribution of the precipitated phase are optimized, and the Laves phase in the alloy is dissolved, eliminating the source of stress concentration, restoring the continuity of the matrix, and dislocation movement is no longer strongly hindered by the Laves phase, and can be distributed and slipped more evenly, thereby improving the strength of the alloy. The uniform slip of dislocations makes the strain distribution of the alloy more uniform during the deformation process, avoiding premature fracture due to local stress concentration and improving the plasticity of the alloy.
[0046] During the additive manufacturing process, there are characteristics of rapid melting and solidification, and the interaction of multiple alloying elements makes it easy to form a coarse columnar crystal structure and significant texture. At the same time, the Laves phase is prone to precipitation, which will limit the performance of the alloy. By selecting the pulse current parameter range of this application (pulse current density 500 - 600 A / mm2, pulse current frequency 50 - 5000 Hz, duty cycle 10 - 50%, pulse current treatment temperature 1080 - 1120 °C, treatment time 10 - 20 min), the Laves phase can be quickly eliminated and the residual stress can be significantly reduced. Particularly importantly, the above parameter range can effectively promote the recrystallization process and stimulate the formation of high-density annealing twins. Under these combined effects, the alloy transforms from coarse columnar crystals to fine equiaxed crystals, weakening the texture strength and reducing the anisotropy of the alloy. It should be noted that annealing twin boundaries (such as Σ3 grain boundaries) can hinder dislocation movement and coordinate plastic deformation between grains, which is beneficial to improving the comprehensive mechanical properties of the alloy, especially significantly improving the plasticity of the alloy while maintaining a relatively high strength.
[0047] Among them, the magnitude of the current density directly affects the processing temperature. If the current density is too high, the Joule heat effect will be too intense, causing the local temperature of the alloy to rise rapidly, which is likely to trigger abnormal grain growth. This is because the excessive temperature provides a great deal of energy for atomic diffusion, intensifying the atomic activity at the grain boundaries and leading to rapid grain growth. Abnormal grain growth is not conducive to improving the properties of the alloy and will reduce the strength and toughness of the alloy. If the current density is too low, it cannot provide sufficient energy for atomic diffusion and dislocation movement, resulting in an insignificant effect of pulsed current treatment and being unable to effectively promote the dissolution of precipitation phases, the elimination of residual stress, and the formation of annealing twins. A higher pulse frequency means an increased number of pulsed current applications per unit time. For the nickel-based superalloy in this application, which contains a special phase (Laves phase) and has a relatively high residual stress, if the pulse frequency is too high, although it can accelerate atomic diffusion and dislocation movement, it will cause the internal microstructure of the alloy to change too violently, resulting in non-uniform microstructure. For example, when promoting the formation of annealing twins, an excessively high frequency may cause twins to grow excessively in local areas while insufficient twins form in other areas, resulting in uneven twin distribution. On the contrary, if the pulse frequency is too low, the recovery time of atoms and dislocations between each pulse application is too long, and the processing efficiency is low, making it difficult to achieve the expected microstructure transformation within a reasonable time, such as being unable to effectively increase the proportion of Σ3 grain boundaries. In the nickel-based superalloy of this application, a short pulsed current treatment time cannot dissolve enough precipitation phases, and it is also difficult to fully eliminate the residual stress. The number and growth degree of annealing twins formed are limited, and the increase in the proportion of Σ3 grain boundaries is not obvious, ultimately resulting in poor improvement of the comprehensive properties of the alloy. However, if the pulsed current treatment time is too long, it will increase production costs and may trigger negative effects such as grain coarsening and excessive element diffusion. The duty cycle reflects the ratio of the conduction time of the pulsed current to the total cycle time within one cycle. For this nickel-based superalloy, if the duty cycle is too large, it is equivalent to a too long duration of the pulsed current, causing the alloy to be in a high-energy input state for a long time, and it is likely to have problems similar to those caused by a too long treatment time, such as grain growth and uneven element diffusion. This will not only affect the microstructure stability of the alloy but also reduce the strength and toughness of the alloy. Conversely, if the duty cycle is too small, the conduction time of the pulsed current is too short, and the energy provided by each pulse is not sufficient to effectively drive processes such as atomic diffusion and dislocation movement, making it impossible to achieve the expected microstructure optimization, such as being difficult to effectively promote the formation of annealing twins and the increase in the proportion of Σ3 grain boundaries.
[0048] In the laser melting deposition process parameters of this application, the laser power is reduced and the scanning speed is increased, resulting in a reduction in the energy input to the molten pool and a significant increase in the solidification rate. At this time, during the rapid solidification of the alloy, atomic diffusion is restricted, and it is easier to form fine and uniform equiaxed crystal structures. The nickel-based superalloy prepared under these optimized parameters contains a large number of high-density dislocations and rich substructures in its microstructure, creating favorable conditions for subsequent pulsed current treatment. Specifically, the movement and interaction of dislocations can lead to local changes in the atomic arrangement, forming embryos of twins. Under the action of pulsed current, atomic diffusion and dislocation movement are intensified, enabling these embryos to rapidly grow into annealing twins; various defects and interfaces in the rich substructures can also serve as the nuclei for twin nucleation, increasing the nucleation rate of annealing twins. The grain boundary between the annealing twins and the parent grains is the Σ3 grain boundary, so the increase in the number of annealing twins increases the proportion of the Σ3 grain boundary.
[0049] In some embodiments, before the step of performing pulsed current treatment on the superalloy, it further includes: using a wire electrical discharge machine to process the superalloy into a sample of a set size; then using 400 - 800# SiC sandpaper to polish the sample; and then using acetone to clean the sample. Among them, the set size is (1.2 - 1.5) mm × (15 - 20) mm × (50 - 55) mm. The size of the sample after additive manufacturing is too large to directly perform pulsed current treatment, and it is machined into a sample size suitable for pulsed current treatment through mechanical processing. Among them, the wire electrical discharge machine is a precise processing equipment with high efficiency, low energy consumption, and can process samples of any shape, so a wire electrical discharge machine is selected to process the sample. The purpose of polishing with sandpaper is to improve the surface quality and increase the dimensional accuracy for subsequent pulsed current treatment.
[0050] After the step of performing pulsed current treatment on the superalloy, it further includes: cooling the treated superalloy by air cooling.
[0051] On the other hand, the present invention provides a nickel-based superalloy, in which the proportion of the Σ3 grain boundary in the nickel-based superalloy > 50%; the elongation after fracture of the nickel-based superalloy > 50%.
[0052] Furthermore, the nickel-based superalloy is the treated nickel-based superalloy obtained by using the treatment method of any one of the above.
[0053] The present invention will be further described below in conjunction with specific examples and comparative examples.
[0054] Example 1
[0055] This example provides a method for optimizing the grain boundaries of a nickel-based superalloy, including the following steps:
[0056] The as-deposited nickel-based superalloy was processed by a wire cutting machine into samples with dimensions of 1.2×15×55 mm, and the wire cutting marks were polished with 400# SiC sandpaper, and the workpiece was cleaned with acetone; then the nickel-based superalloy after cleaning treatment was subjected to pulsed current treatment. After the treatment, the pulsed power supply was disconnected, and the workpiece was taken out after air cooling to room temperature to obtain the treated nickel-based superalloy.
[0057] Among them, by weight percentage, the chemical composition of the nickel-based superalloy before treatment is as follows:
[0058] Element Al Ti Nb W Mo Cr Co Fe C Ni wt% 1.6 0.8 5.2 1.2 2.3 18.9 9.1 9.3 0.03 Balance
[0059] The as-deposited nickel-based superalloy was prepared by a laser melting deposition process; among them, the parameters of the laser melting deposition process are: the laser power is 1000 w; the laser scanning speed is 9 mm / s; the powder feeding rate is 7 g / min; the Z-axis lifting height is 0.8 mm.
[0060] Among them, the parameters of the pulsed current treatment are: the current density is 600 A / mm 2 ; the current frequency is 5000 Hz; the duty cycle is 50%; the treatment temperature is 1100 °C; the treatment time is 15 min.
[0061] The EBSD (Electron Backscattering Diffraction) method was used to observe and analyze the grain boundary characteristic distribution and the proportion of Σ3 grain boundaries in the laser additive manufactured nickel-based superalloy before and after the pulsed current treatment in this example. The results are shown in Figure 1 , Figures 2 and 4 respectively. It can be seen that the as-deposited sample (i.e., before the pulsed current treatment) does not contain Σ3 grain boundaries. After the pulsed current treatment, the proportion of Σ3 grain boundaries in the alloy reaches 56.5%, and the optimization effect of its grain boundary characteristic distribution is obvious.
[0062] In this example, the pulsed current treatment temperature is set at 1100 °C. The higher temperature can significantly improve the activity of atoms and reduce the energy barrier for atomic diffusion at grain boundaries. According to the grain boundary migration theory, the grain boundary migration rate is closely related to temperature and follows the Arrhenius relationship, that is (where M is the boundary migration rate, which is the pre-exponential coefficient, Q is the activation energy, and R is the gas constant); therefore, as the temperature T increases, the grain boundary migration rate increases, and then the grain boundary migration rate is enhanced, providing power for recrystallization and grain boundary evolution. During the grain boundary migration process, the irregularity of atomic arrangement increases, creating conditions for the formation of Σ3 grain boundaries. At the same time, the room temperature tensile properties of the laser additive manufactured nickel-based superalloy samples before and after the pulsed current treatment in this example were tested, and the elongation after fracture results are shown in Figure 3As shown, it can be seen that the elongation after fracture of the sample before pulsed current treatment is 3.5%, and the elongation after fracture of the alloy after pulsed current treatment is 59.5%, with an increase of 160%.
[0063] Example 2
[0064] This example provides a method for optimizing the grain boundaries of a nickel-based superalloy, including the following steps:
[0065] Use a wire cutting machine to process the as-deposited nickel-based superalloy into samples with dimensions of 1.5×20×50 mm, polish the wire cutting marks with 800# SiC sandpaper, and clean the workpiece with acetone; then perform pulsed current treatment on the cleaned nickel-based superalloy. After the treatment is completed, disconnect the pulsed power supply, and take out the workpiece after it has air-cooled to room temperature to obtain the treated nickel-based superalloy.
[0066] Among them, by weight percentage, the chemical composition of the nickel-based superalloy before treatment is as follows:
[0067] Element Al Ti Nb W Mo Cr Co Fe C Ni wt% 3.5 1.3 5.8 0.7 3.2 17 10 10.8 0.02 Balance
[0068] The as-deposited nickel-based superalloy is prepared by a laser melting deposition process; among them, the parameters of the laser melting deposition process are: laser power is 1000 w; laser scanning speed is 9 mm / s; powder feeding rate is 7 g / min; Z-axis lifting height is 0.8 mm.
[0069] Among them, the parameters of the pulsed current treatment are: current density 500 A / mm 2 ; current frequency is 5000 Hz; duty cycle is 10%; treatment temperature is 1120 °C; treatment time is 20 min.
[0070] Use the EBSD (Electron Backscattering Diffraction) method to observe and analyze the laser additive manufactured nickel-based superalloy after pulsed current treatment in this example. According to Figure 2 it can be known that the proportion of Σ3 grain boundaries is 43.8%, and the optimization effect of its grain boundary characteristic distribution is obvious. In this example, the elongation after fracture of the sample before pulsed current treatment is 3.5%, and the elongation after fracture of the alloy after pulsed current treatment is 46.3% ( Figure 3 ), with an increase of 122.2%.
[0071] Comparative Example 1
[0072] This comparative example provides a method for optimizing the grain boundaries of a nickel-based superalloy, including the following steps:
[0073] The as-deposited nickel-based superalloy was processed by a wire cutting machine into samples with dimensions of 1.2×15×55 mm, and the wire cutting marks were polished with 400# SiC sandpaper, and the workpiece was cleaned with acetone; then the cleaned nickel-based superalloy was heat-treated at 1150 °C for 60 min, and after cooling the workpiece to room temperature in air, the treated nickel-based superalloy was taken out.
[0074] Among them, by weight percentage, the chemical composition of the nickel-based superalloy before treatment is as follows:
[0075] Element Al Ti Nb W Mo Cr Co Fe C Ni wt% 1.6 0.8 5.2 1.2 2.3 18.9 9.1 9.3 0.03 Balance
[0076] The as-deposited nickel-based superalloy was prepared by a laser melting deposition process; among them, the parameters of the laser melting deposition process were: the laser power was 1000 w; the laser scanning speed was 9 mm / s; the powder feeding rate was 7 g / min; the Z-axis lifting height was 0.8 mm.
[0077] The Electron Backscattering Diffraction (EBSD) method was used to observe and analyze the grain boundary characteristic distribution in the laser additive manufactured nickel-based superalloy after heat treatment in this comparative example. The results are as Figure 6 shown. It can be seen that the as-deposited sample (i.e., before pulsed current treatment) does not contain Σ3 grain boundaries, and the proportion of Σ3 grain boundaries in the alloy after traditional heat treatment is 23.6% ( Figure 2 ), which is much lower than that of the laser additive manufactured nickel-based superalloy after pulsed current treatment. This is because traditional heat treatment mainly relies on thermal activation to drive atomic diffusion and grain boundary migration, and the grain boundary migration rate is relatively slow, which is not conducive to the formation of Σ3 grain boundaries. At the same time, long-term high-temperature heat treatment leads to abnormal grain growth, making it difficult to form a large number of Σ3 grain boundaries. At the same time, the room temperature tensile properties of the laser additive manufactured nickel-based superalloy sample after heat treatment in this comparative example were tested, and the elongation after fracture results are as Figure 3 shown. It can be seen that the elongation after fracture of the alloy after traditional treatment is 28.1%; this is because the proportion of Σ3 grain boundaries is low, and at the same time the grain size increases significantly, making it difficult for adjacent grains to coordinate deformation, which is not conducive to the uniform distribution and slip of dislocations, and is prone to local stress concentration during tensile testing, resulting in premature fracture of the alloy, thus limiting the improvement of the elongation.
[0078] Comparative Example 2
[0079] This comparative example provides a method for optimizing the grain boundaries of nickel-based superalloys, including the following steps:
[0080] The as-deposited nickel-based superalloy was processed by a wire cutting machine into samples with dimensions of 1.2×15×55 mm, and the wire cutting marks were polished with 400# SiC sandpaper, and the workpiece was cleaned with acetone; then the cleaned nickel-based superalloy was subjected to pulsed current treatment. After the treatment, the pulsed power supply was disconnected, and the workpiece was taken out after air cooling to room temperature to obtain the treated nickel-based superalloy.
[0081] Among them, by weight percentage, the chemical composition of the nickel-based superalloy before treatment is as follows:
[0082] Element Al Ti Nb W Mo Cr Co Fe C Ni wt% 1.6 0.8 5.2 1.2 2.3 18.9 9.1 9.3 0.03 Balance
[0083] The as-deposited nickel-based superalloy was prepared by a laser melting deposition process; among them, the parameters of the laser melting deposition process are: laser power is 1000 w; laser scanning speed is 9 mm / s; powder feeding rate is 7 g / min; Z-axis lifting height is 0.8 mm.
[0084] Among them, the parameters of the pulsed current treatment are: current density 400 A / mm 2 ; current frequency is 5000 Hz; duty cycle is 50%; treatment temperature is 1050 °C; treatment time is 10 min.
[0085] The EBSD (Electron Backscattering Diffraction) method was used to observe and analyze the grain boundary characteristic distribution in the laser additive manufactured nickel-based superalloy after pulsed current treatment in this comparative example. The results are shown respectively as Figure 7 shown. It can be seen that there is no Σ3 grain boundary in the alloy after pulsed current treatment; this is mainly because the applied pulsed current density is small, resulting in a treatment temperature lower than 1100 °C, insufficient atomic activity, and a significant reduction in the grain boundary migration rate. The recrystallization process requires rapid diffusion of atoms and migration of grain boundaries to form a new grain structure. At low temperatures, atomic diffusion is slow, new grains are difficult to nucleate and grow, and the recrystallization process cannot be completed, so conditions for the formation of Σ3 grain boundaries cannot be created. At the same time, the room temperature tensile properties of the laser additive manufactured nickel-based superalloy samples before and after pulsed current treatment in this comparative example were tested, and the elongation after fracture of the treated alloy was 39.5% ( Figure 3 ), higher than that of the as-deposited sample, but much lower than that of the alloy after pulsed current treatment in Example 1. This is because the dissolution of the Laves phase eliminates the stress concentration source. Therefore, compared with the as-deposited sample, the elongation of the sample in this comparative example increases significantly. However, compared with the sample in Example 1, the sample in this comparative example does not form a large number of Σ3 grain boundaries, and it is difficult for dislocations between different grains to coordinate deformation during tensile testing, which easily leads to local stress concentration and causes the alloy to fracture prematurely, thus limiting the increase in elongation.
[0086] Comparative Example 3
[0087] This comparative example provides a method for optimizing the grain boundaries of a nickel-based superalloy, including the following steps:
[0088] Use a wire cutting machine to process the as-deposited nickel-based superalloy into samples with dimensions of 1.2×15×55 mm, and use 400# SiC sandpaper to polish the wire cutting marks, and clean the workpiece with acetone; then perform pulsed current treatment on the cleaned nickel-based superalloy. After the treatment is completed, disconnect the pulsed power supply, and take out the workpiece after it has air-cooled to room temperature to obtain the treated nickel-based superalloy.
[0089] Among them, by weight percentage, the chemical composition of the nickel-based superalloy before treatment is as follows:
[0090] Element Al Ti Nb Mo Cr Fe C Ni wt% 0.6 0.9 5.1 2.3 19 18.5 0.04 Balance
[0091] The as-deposited nickel-based superalloy is prepared by a laser melting deposition process; among them, the parameters of the laser melting deposition process are: the laser power is 1000 w; the laser scanning speed is 9 mm / s; the powder feeding rate is 7 g / min; the Z-axis lifting height is 0.8 mm.
[0092] Among them, the parameters of the pulsed current treatment are: the current density is 600 A / mm 2 ; the current frequency is 5000 Hz; the duty cycle is 50%; the treatment temperature is 1100 °C; the treatment time is 15 min.
[0093] Use the EBSD (Electron Backscattering Diffraction) method to observe and analyze the grain boundary characteristic distribution in the laser additive manufactured nickel-based superalloy after the pulsed current treatment of this comparative example. The results are as follows Figure 8 shown. It can be seen that after being treated with the same pulsed parameters as in Example 1, the proportion of Σ3 grain boundaries in the alloy reaches 41.3% ( Figure 2 ), and the optimization effect of its grain boundary characteristic distribution is far less than that of Example 1. At the same time, the room temperature tensile properties of the laser additive manufactured nickel-based superalloy samples before and after the pulsed current treatment of this comparative example are tested, and the elongation after fracture of the treated alloy is 44.5% ( Figure 3 ), which is much lower than the alloy after the pulsed current treatment in Example 1.
[0094] In this comparative example, an alloy composition different from that of Example 1 was prepared, the contents of Al and Ti were changed, the Fe content was increased, and the Co content was decreased, so that the SFE of the alloy increased. After the SFE increased, the energy required to form stacking faults increased, and it became more difficult to form stacking faults in the material. The existence of stacking faults is the basis for the formation of twins. Therefore, in Comparative Example 3, it is more difficult for the alloy to form annealing twins, which in turn leads to a decrease in the number of formed Σ3 grain boundaries (the grain boundaries between annealing twins and the parent grains), and finally the proportion of Σ3 grain boundaries in the treated alloy is lower than that in Example 1.
[0095] It is easy for those skilled in the art to understand that, on the premise of no conflict, the advantageous technical features of the above various methods can be freely combined and superimposed.
[0096] The above are only the preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above is only the preferred implementation manner of the present invention. It should be pointed out that for those of ordinary skill in the art, without departing from the technical principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A treatment method for optimizing the grain boundaries of nickel-based superalloys, characterized in that, It includes the following steps: Perform pulsed current treatment on the nickel-based superalloy so that the proportion of Σ3 grain boundaries in the treated nickel-based superalloy > 50%.
2. The method for treating the grain boundaries of the optimized nickel-based superalloy according to claim 1, wherein The nickel-based superalloy is an additive manufacturing nickel-based superalloy; Preferably, the additive manufacturing nickel-based superalloy is prepared by a laser melting deposition process; More preferably, the parameters of the laser melting deposition process are: laser power is 900 - 1000w; laser scanning speed is 8 - 10mm / s; powder feeding rate is 6 - 7g / min; Z-axis lifting height is 0.7 - 0.9mm.
3. The method for treating the grain boundary of the optimized nickel-based superalloy according to claim 1 or 2, characterized in that, By weight percentage, the chemical composition of the nickel-based superalloy is: Al 1.5wt% - 3.6wt%, Ti 0.5wt% - 1.5wt%, Nb 5wt% - 6wt%, W 0.5wt% - 1.5wt%, Mo 2.5wt% - 3.5wt%, Co 9wt% - 10wt%, Cr 17wt% - 19wt%, Fe 9wt% - 11wt%, C 0.02wt% - 0.03wt%, and the balance is Ni.
4. The method for treating the grain boundary of the optimized nickel-based superalloy according to claim 1, characterized in that, The parameters of the pulsed current treatment are as follows: Current density: 500 - 600 A / mm 2 ; Current frequency: 50 - 5000 Hz; Duty cycle: 10 - 50%; Treatment temperature: 1080 - 1120 °C; Treatment time: 10 - 20 min.
5. The treatment method for optimizing the grain boundaries of a nickel-based superalloy according to claim 1, characterized in that Before the step of performing pulsed current treatment on the superalloy, it further includes: Process the superalloy into a sample with a set size; Preferably, use a wire electrical discharge machine to process the superalloy into a sample with a set size; Preferably, the set size is (1.2 - 1.5)mm × (15 - 20)mm × (50 - 55)mm.
6. The processing method for optimizing the grain boundaries of the nickel-based superalloy according to claim 5, characterized in that, After the step of processing the superalloy into a sample with a set size, it further includes: Perform grinding treatment and cleaning treatment on the sample in sequence; Preferably, use 400 - 800# SiC sandpaper to perform grinding treatment on the sample; Preferably, use acetone to perform cleaning treatment on the sample.
7. The processing method for optimizing the grain boundaries of the nickel-based superalloy according to claim 1, characterized in that, After the step of performing pulsed current treatment on the superalloy, it further includes: cooling treatment on the treated superalloy; Preferably, the cooling treatment is performed by air cooling.
8. A nickel-based superalloy, characterized in that, The proportion of Σ3 grain boundaries in the nickel-based superalloy > 50%; the elongation after fracture of the nickel-based superalloy > 50%.
9. The nickel-based superalloy according to claim 8, wherein, The nickel-based superalloy is the treated nickel-based superalloy obtained by using the treatment method described in any one of claims 1 - 7.